Appropriating Care and Hijacking Desire: Thought and Praxis in Human Services Under 21st Century Capitalism. Issue 3 (2nd September 2017) - Skott-Myhre, Hans; McDonald, Brad; Skott-Myhre, Kathleen S. G.
ABSTRACT: In this article, we trace the rise of neoliberalism and its impacts on the historical role of human services within the academy and the community. We ask whether we can re-think and re-envision a 21st century academy rooted in the material actualities of daily living and connected in very real ways to the struggles of those Human Services was designed to serve. Finally, we propose that Human Services could have a significant role to play in developing new modes of value that could lead to new modes of thought and new avenues of praxis.